1997
DOI: 10.1046/j.1365-2362.1997.2250774.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters in cerebrospinal fluid reflect pathological activity

Abstract: The excitatory transmitters glutamate and aspartate become toxic whenever their extracellular levels are increased because of neuronal, glial and endothelial impairment. Taurine, a volume-regulating amino acid, is released upon excitotoxin-induced cell swelling. Our aim was to investigate if glutamate and aspartate in cerebrospinal fluid (CSF) reveal neuropathology in neurological patients, and if taurine unmasks glutamate-mediated toxicity. Glutamate and aspartate are doubled in viral meningitis, acute multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(75 citation statements)
references
References 40 publications
3
69
2
1
Order By: Relevance
“…Indeed, it has been shown that cerebrospinal fluid glutamate levels are increased during relapses in RR-MS patients and highly increased in SP-MS patients who had an increase of at least 1 point in the EDSS score during the last 6 months as compared with SP-MS patients without any change in the EDSS score (13,62). Accordingly, it has been demonstrated that glutamate receptor antagonists and inhibitors of glutamate transmission were efficient in reducing axonal damage, death of oligodendrocytes, and ameliorating clinical EAE (15)(16)(17)(18)(19)45).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that cerebrospinal fluid glutamate levels are increased during relapses in RR-MS patients and highly increased in SP-MS patients who had an increase of at least 1 point in the EDSS score during the last 6 months as compared with SP-MS patients without any change in the EDSS score (13,62). Accordingly, it has been demonstrated that glutamate receptor antagonists and inhibitors of glutamate transmission were efficient in reducing axonal damage, death of oligodendrocytes, and ameliorating clinical EAE (15)(16)(17)(18)(19)45).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recent studies suggest that excitotoxicity may play an important role in the pathogenesis of both MS and EAE. Increased levels of glutamate were observed in the cerebrospinal fluid from MS patients, 6 and a correlation was shown between the cerebrospinal fluid glutamate and the disease activity and severity. 7 CNS-infiltrating macrophages and activated microglia are probably the major sources because these cells release large quantities of glutamate after activation in vitro.…”
mentioning
confidence: 97%
“…It is widely accepted that the most common pathological abnormality in MS is an inflammatory demyelination in the CNS, but recent studies have highlighted the additional presence of axonal damage (37,38). The cause of demyelination and axonal damage remains unclear, but several lines of evidence support the possibility that glutamate-induced excitotoxicity plays a role in these pathological changes in MS. Glutamate concentration in the cerebrospinal fluid (CSF) is reported to be elevated in patients suffering from acute MS (39,40). In EAE, glutamate-metabolizing enzymes, glutamine synthetase, and glutamate dehydrogenase are downwardly regulated in astrocytes (41).…”
mentioning
confidence: 99%